Long-Term Health Outcomes and Health-Related Quality of Life in Adolescents from a Cohort of Extremely Premature Infants Born at Less Than 27 Weeks of Gestation in Northern Germany - Stahlmann, Nele; Eisemann, Nora; Thyen, Ute; Herting, Egbert; Rapp, Marion (Neuropediatrics, 2016)
Background Little is known about the psychosocial development and health-related quality of life (HRQOL) of extremely preterm infants once they are adolescents.Methods The regional population-based study cohort included 90 extremely premature infants (< 27+0 gestational weeks) born between January 1997 and December 1999 in the German state of Schleswig-Holstein. In addition to a neurological and cognitive Wechsler Intelligence Scale for Children, 4th edition assessment, self- and parent-reported psychological problems (Strengths and Difficulties Questionnaire), and health-related quality of life (KINDLR) were obtained and compared with a general population of 3,737 adolescents using data from a German Health Interview and Examination Survey for Children and Adolescents (KiGGS survey 2003–2006, Robert Koch Institute, Germany).Results Overall, 72 of the 90 surviving adolescents and their families (80.0%) participated in this study (mean age: 15.7 years; range: 14.2–17.2). A total of 22 adolescents (30.6%) did not have any neurosensory or cognitive limitations, whereas 31 adolescents (43.1%) were affected by multiple impairments. Parent-reported psychological problems were more common in the study cohort for the total difficulties score (11.3 points [standard deviation, SD: 5.9] vs. 7.7 points [SD: 5.0], p < 0.001) and for three of the five domains (emotional symptoms, hyperactivity-inattention, peer relationship problems) compared with the KiGGS reference population. In contrast, the rate of self-reported “abnormal” psychological problems was similar to the reference population. Parent-reported HRQOL was significantly lower in the study cohort for the total score (−3.7 points, p < 0.05) and for three of six subscales (emotional wellbeing, p < 0.05; self-esteem, p < 0.001, and wellbeing with regard to friends/friendship, p < 0.001). The adolescents themselves reported an HRQOL similar to that of the KiGGS reference population, though they rated their HRQOL higher for wellbeing with regard to families (p < 0.001) and wellbeing with regard to school/all-day function (p < 0.001). Overall, the parent- and self-reported HRQOL results were not associated with maternal education or disability status but were associated with adolescents' psychological problems.Conclusion Concordant with the high rate of functional and cognitive limitations, parents of adolescents who were born extremely prematurely faced more psychological problems in their children and reported a lower HRQOL compared with the KiGGS reference population. The adolescents themselves did not recognize these differences. However, having psychological problems was associated with lower self- and parent-reported HRQOL results.
Keywords: prematurity; quality of life; adolescence; psychological problems; parent-report; self-report; KiGGS